Responding to Manitoba’s “Right to Read” Report - Honeyford, Michelle; Stouffer, Joe; Watt, Jennifer; Janzen, Melanie D.; Du, Xiaoxiao; Ntelioglou, Burcu; Michalovich, Amir (Journal of Teaching and Learning, 2026)
In fall 2025, the Manitoba Human Rights Commission released a report, The ABCs of a Rights-Based Approach to Teaching Reading: Phase One Report–Findings and Recommendations, stemming from its Special Project on the Human Rights Issues affecting Students with Reading Disabilities in Manitoba’s Education system. While we, a coalition of Manitoba literacies researchers and teacher educators, welcomed the report’s championing of every child’s right to learn to read (and write) and its calls for accessible support for all literacy learners, we took issue with the methodology of the report, biases and flaws within its findings, and questioned the appropriateness and soundness of many of the report’s recommendations. In this commentary, we share the contents of our letter to the Commission to point out that the research cited in the report and its “rights-based” approach are deeply flawed and, if enacted, will create greater inequities in access to education for children.